Influence of canopy-applied chitosan on the composition of organic cv. Sangiovese and Cabernet Sauvignon berries and wines. (1st November 2016) - Tessarin, Paola; Chinnici, Fabio; Donnini, Silvia; Liquori, Enrico; Riponi, Claudio; Rombolà, Adamo Domenico
Highlights: Canopy applied chitosan influenced the composition of cv. Cabernet Sauvignon grapes. Grapes from cv. Sangiovese were only slightly affected by chitosan. Some flavanols, amino acids and amines were significantly higher in treated cv. Cabernet Sauvignon grapes. The triggering by chitosan of plant Systemic Acquired Resistance has been proposed. Abstract: The effects of canopy-applied chitosan on grapes and derived wine were evaluated in an organically managed mature vineyard. The experiment was performed on Sangiovese and Cabernet Sauvignon red grape cultivars, the application of a chitosan solution was compared to water spraying. Each treatment was applied 3 times (beginning and end of veraison, and pre-harvest) in a randomized block experimental design. Significant differences in (+)-catechin, (−)-epicatechin and procyanidin B2 amounts in berries and wines were detected in Cabernet Sauvignon but not in Sangiovese. Chitosan did not influence the berry skin anthocyanin and flavonol amount or t -resveratrol concentration in both skins and wines. A considerable increase in γ-aminobutyric acid (GABA), together with some other amino acids, ammonium and amines was observed in the berry flesh of cv. Cabernet Sauvignon. The increase in phenolic acids and nitrogenous compounds, especially GABA, in the pulp of Cabernet Sauvignon grapes suggests changes in stress response.